A Faustian pact: Has the EU-Turkey deal undermined the EU's own security?. Issue 3 (27th May 2018) - Kfir, Isaac
Abstract: This article argues that because the EU is more concerned with Turkey serving as a barrier to those seeking refuge in Europe, it has empowered the Erdoğan regime to continue to adopt and implement measures that undermine Turkish democracy. Such a myopic approach has allowed Erdoğan to usurp more power, which has had dire consequences for European security as it means that Europe would share a border a with a nondemocratic state. It also makes it harder for the EU to work with Ankara, because if the EU criticizes or imposes sanctions it makes it more likely that Erdoğan would gravitate toward Russia and Iran, thus further undermining European security, as the EU has a complex relationship with these two countries, particularly Russia. It is only by taking some tough decisions on migration that the EU could solve the insecurity challenge that Turkey poses.